2018
DOI: 10.1002/2017gl076319
|View full text |Cite
|
Sign up to set email alerts
|

On the Chaotic Variability of Deep Convection in the Mediterranean Sea

Abstract: Chaotic intrinsic variability is a fundamental driver of the oceanic variability. Its understanding is key to interpret observations, evaluate numerical models, and predict the future ocean and climate. Here we study intrinsic variability of deep convection in the northwestern Mediterranean Sea using an ensemble eddy‐resolving hindcast simulation over the period 1979–2013. We find that the variability of deep convection is mostly forced but also, to a considerable extent, intrinsic. The intrinsic variability c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 58 publications
0
30
0
1
Order By: Relevance
“…Moreover, the climatological year forcing strategy used here and by several previous authors (Grégorio et al, ; Li et al, ; Penduff et al, ) allows a first assessment of the OIV contribution but only under these given atmospheric (climatological) conditions. Performing an ensemble of multiannual simulations driven by the same interannual high‐frequency atmospheric forcing but with perturbed initial conditions (as done by several authors, Leroux et al, ; Sérazin et al, ; Waldman et al, ) would allow us to disentangle and study both the intrinsic and atmospheric contributions under realistic atmospheric forcing and thus to more robustly assess the contribution of OIV on the SVU interannual variability. More generally, the strong OIV revealed here requires ensemblist approaches for better statistical significance of SVU modeling studies that would help to further quantify and understand the effect of OIV on the SVU, as concluded for other processes (Waldman et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the climatological year forcing strategy used here and by several previous authors (Grégorio et al, ; Li et al, ; Penduff et al, ) allows a first assessment of the OIV contribution but only under these given atmospheric (climatological) conditions. Performing an ensemble of multiannual simulations driven by the same interannual high‐frequency atmospheric forcing but with perturbed initial conditions (as done by several authors, Leroux et al, ; Sérazin et al, ; Waldman et al, ) would allow us to disentangle and study both the intrinsic and atmospheric contributions under realistic atmospheric forcing and thus to more robustly assess the contribution of OIV on the SVU interannual variability. More generally, the strong OIV revealed here requires ensemblist approaches for better statistical significance of SVU modeling studies that would help to further quantify and understand the effect of OIV on the SVU, as concluded for other processes (Waldman et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Performing an ensemble of multiannual simulations driven by the same interannual high‐frequency atmospheric forcing but with perturbed initial conditions (as done by several authors, Leroux et al, ; Sérazin et al, ; Waldman et al, ) would allow us to disentangle and study both the intrinsic and atmospheric contributions under realistic atmospheric forcing and thus to more robustly assess the contribution of OIV on the SVU interannual variability. More generally, the strong OIV revealed here requires ensemblist approaches for better statistical significance of SVU modeling studies that would help to further quantify and understand the effect of OIV on the SVU, as concluded for other processes (Waldman et al, ). Fourth, the realism of atmospheric and hydrological forcing in our model could be further improved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Waldman, Herrmann, et al () showed that intrinsic variability has a strong impact on the timing and geographical extent of a convective event but has little impact on the rate of convection in the constrained 2012–2013 case. Waldman et al () further showed that intrinsic variability also explains a significant fraction of the deep convection interannual variability, although it has only modest impacts on the long‐term mean state.…”
Section: Major Outcomesmentioning
confidence: 99%